Local and systemic effects of co-stimulatory blockade using cytotoxic T lymphocyte antigen-4-immunoglobulin in dinitrofluorobenzene- and oxazolone-induced contact hypersensitivity in mice - Christensen, A D (Blackwell Science Inc, 2013)
Cytotoxic T lymphocyte-associated antigen-4 (CTLA-4)-immunoglobulin (Ig) has immunosuppressive properties both in vivo and in vitro, but much is still unknown about the mechanisms by which CTLA-4-Ig exerts its immunosuppressive activities in vivo. The aim of this study was to investigate the effect of CTLA-4-Ig in a mouse model of contact hypersensitivity (CHS). The inflammatory response in the presence or absence of CTLA-4-Ig was evaluated by measuring the increase in ear thickness in sensitized animals after challenge. We observed a dose-dependent suppression of the ear swelling in both dinitrofluorobenzene (DNFB)- and oxazolone-induced CHS. The suppressive effect was still present 3 weeks after administration, even in the absence of circulating levels of CTLA-4-Ig. It was further shown that CTLA-4-Ig inhibits activation of T cells in the draining lymph node after sensitization and affects the maturation level of both dendritic cells and B cells. Furthermore, CTLA-4-Ig reduces infiltration of activated CD8(+) T cells into the inflamed ear tissue and suppresses both local and systemic inflammation, as illustrated by reduced expression of cytokines and chemokines in the inflamed ear and a reduced level of acute-phase proteins in circulation. Finally, our results suggest that CTLA-4-Ig has a mainly immunosuppressive effect during the sensitization phase. We conclude that CTLA-4-Ig induces long-term immunosuppression of both DNFB- and oxazolone-induced inflammation and our data are the first to compare the effect of this compound in both DNFB- and oxazolone-induced CHS and to show that CTLA-4-Ig exerts an immunosuppressive effect on both local and systemic inflammatory mediators which is mediated principally during the sensitization phase.